2021
DOI: 10.1002/cne.25197
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitectural characteristics associated with cognitive flexibility in raccoons

Abstract: With rates of psychiatric illnesses such as depression continuing to rise, additional preclinical models are needed to facilitate translational neuroscience research. In the current study, the raccoon (Procyon lotor) was investigated due to its similarities with primate brains, including comparable proportional neuronal densities, cortical magnification of the forepaw area, and cortical gyrification. Specifically, we report on the cytoarchitectural characteristics of raccoons profiled as high, intermediate, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Our study is a rare demonstration of a relation between neuron number or neuron density and a particular cognitive ability. Previous within-species comparisons showed that neuron number in multiple brain regions did not predict performance on a battery of behavioural tasks in mice [135], and though raccoons who performed best on a puzzle box task had more cells in their hippocampus than lower performing individuals, this difference may have been driven by glial cells [136]. However, crossspecies comparisons in primates and birds suggest that neuron number has more behavioural explanatory power than cranial capacity, based on the correlation between cortical or pallial neuron number and performance on a self-control task [71].…”
Section: Discussionmentioning
confidence: 93%
“…Our study is a rare demonstration of a relation between neuron number or neuron density and a particular cognitive ability. Previous within-species comparisons showed that neuron number in multiple brain regions did not predict performance on a battery of behavioural tasks in mice [135], and though raccoons who performed best on a puzzle box task had more cells in their hippocampus than lower performing individuals, this difference may have been driven by glial cells [136]. However, crossspecies comparisons in primates and birds suggest that neuron number has more behavioural explanatory power than cranial capacity, based on the correlation between cortical or pallial neuron number and performance on a self-control task [71].…”
Section: Discussionmentioning
confidence: 93%
“…The emergence of VENs is not related to the relative brain size or encephalization of the studied species ( Allman et al, 2010 ). There is a possibility that VENs might be associated with the mechanical challenges associated with larger, gyrencephalic brains along with other evolutionary adaptations ( Jacob et al, 2021 ). Human VENs with sparse dendritic trees and symmetric ascending and descending main shafts were considered computationally simple compared to layer V pyramidal neurons, likely receiving few inputs within individual minicolumns for a rapid cortical radial signal transmission ( Watson et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Von Economo neurons (VENs) have a peculiar phylogenetic and ontogenetic development and are characterized by an elongated spindle-shaped or rod-shaped cell body mainly found in the cortical layer V of restricted brain areas of some species, including humans and other primates, but not in all mammals ( Nimchinsky et al, 1995 ; Allman et al, 2005 , 2010 ; Hakeem et al, 2009 ; Cauda et al, 2014 ; Raghanti et al, 2015 ; Hodge et al, 2020 ; Jacob et al, 2021 ). In humans, VENs have been reported mainly in the anterior cingulate cortex (ACC) and frontoinsular cortex (FI; Raghanti et al, 2015 ; Banovac et al, 2019 , 2021 ; Correa-Júnior et al, 2020 and references therein), but also in the dorsolateral prefrontal cortex (Brodmann area 9; Fajardo et al, 2008 ) and in the medial frontopolar prefrontal cortex (Brodmann area 10; González-Acosta et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For coma patients who are incapable of saying anything or any motor responses whatsoever, measuring brain activity provides the last resort for assessing their consciousness. Surprisingly, it has been found that patients who were thought to be 11 (Critchley and Seth, 2012;Butti et al, 2013) 12 (Lamme and Roelfsema, 2000;Crick and Koch, 2003) 13 It is not very clear which animals have von Economo neurons and which don't; Jacob et al (2021) have recently claimed to find them even in raccoons.…”
Section: How Can We Know Something Is Consciousmentioning
confidence: 99%